Achieving measles control: lessons from the 2002–06 measles control strategy for Uganda - Mbabazi, William B.; Nanyunja, Miriam; Makumbi, Issa; Braka, Fiona; Baliraine, Frederick N.; Kisakye, Annet; Bwogi, Josephine; Mugyenyi, Possy; Kabwongera, Eva; Rosamund, F Lewis (Health policy and planning, 2009)
Background The 2002–06 measles control strategy for Uganda was implemented to strengthen routine immunization, undertake large-scale catch-up and follow-up vaccination campaigns, and to initiate nationwide case-based, laboratory-backed measles surveillance. This study examines the impact of this strategy on the epidemiology of measles in Uganda, and the lessons learnt. Methods Number of measles cases and routine measles vaccination coverage reported by each district were obtained from the National Health Management Information System reports of 1997 to 2007. The immunization coverage by district in a given year was calculated by dividing the number of children immunized by the projected population in the same age category. Annual measles incidence for each year was derived by dividing the number of cases in a year by the mid-year projected population. Commercial measles IgM enzyme-linked immunoassay kits were used to confirm measles cases. Results Routine measles immunization coverage increased from 64% in 1997 to 90% in 2004, then stabilized around 87%. The 2003 national measles catch-up and 2006 follow-up campaigns reached 100% of children targeted with a measles supplemental dose. Over 80% coverage was also achieved with other child survival interventions. Case-based measles surveillance was rolled out nationwide to provide continuous epidemiological monitoring of measles occurrence. Following a 93% decline in measles incidence and no measles deaths, epidemic resurgence of measles occurred 3 years after a measles campaign targeting a wide age group, but no indigenous measles virus (D10) was isolated. Recurrence was delayed in regions where children were offered an early second opportunity for measles vaccination. Conclusion The integrated routine and campaign approach to providing a second opportunity for measles vaccination is effective in interrupting indigenous measles transmission and can be used to deliver other child survival interventions. Measles control can be sustained and the inter-epidemic interval lengthened by offering an early second opportunity for measles vaccination through other health delivery strategies.